Vasopressors and inotropes in cardiogenic shock patients: an analysis of the MIMIC-IV database - Sasmita, Bryan Richard; Wang, ChuanYing; Xie, Siyuan (Frontiers in Cardiovascular Medicine, 2023)
Introduction- Pharmacological support has become the mainstay therapy in patients with cardiogenic shock (CS). Unfortunately, the clinical benefits of such potent drugs remain unclear, therefore, the present study aims to elucidate the safety and efficacy of vasoactive agents in CS patients. Methods- Medical Information Mart for Intensive Care (MIMIC) IV databases were used for this retrospective study. The primary outcome of this study was 30-day all-cause mortality. The subgroup analysis of was the relationship between the combined use of vasopressors and inotropes and 30-day all-cause mortality. Results- A total of 2216 patients diagnosed with CS were enrolled in this study. The non-survivors group was more likely to be older, presented with chronic kidney disease, have a lower systolic blood pressure, lower heart rate, and higher respiratory rate (all p<0.005). In the multivariate Cox regression analysis, only dopamine [HR (95%CI): 1.219 (1.003-1.482)], norepinephrine [HR (95%CI): 2.528 (1.829-3.493)], and milrinone [HR (95%CI): 0.664 (0.512-0.861)] remained an independent predictor for 30-day all-cause mortality. Furthermore, a subgroup analysis was performed and found that no statistically significant difference between no vasopressor/inotrope use and 1 vasopressor/inotrope use (p=0.107). Meanwhile, a substantial deterioration of cumulative survival was observed when a combination of 2 or more vasopressors/inotropes was used in CS patients in comparison with no vasopressor/inotrope or only 1 vasopressor/inotrope use (all p<0.05). Conclusions- Using vasopressors/inotropes agents was associated with a higher risk of 30-day all-cause mortality in CS patients. In addition, only milrinone was associated with a better prognosis among the available vasoactive agents.